Is chronic malnutrition associated with an increase in malaria incidence? A cohort study in children aged under 5 years in rural Gambia - Wilson, A.L.; Bradley, J.; Kandeh, B.; Salami, K.; D’Alessandro, U.; Pinder, M.; Lindsay, S.W. (Parasites and Vectors, 2018)
Background Malnutrition is common in children in sub-Saharan Africa and is thought to increase the risk of infectious diseases, including malaria. The relationship between malnutrition and malaria was examined in a cohort of 6–59 month-old children in rural Gambia, in an area of seasonal malaria transmission. The study used data from a clinical trial in which a cohort of children was established and followed for clinical malaria during the 2011 transmission season. A cross-sectional survey to determine the prevalence of malaria and anaemia, and measure the height and weight of these children was carried out at the beginning and end of the transmission season. Standard anthropometric indices (stunting, wasting and underweight) were calculated using z-scores. Results At the beginning of the transmission season, 31.7% of children were stunted, 10.8% wasted and 24.8% underweight. Stunting was more common in Fula children than other ethnicities and in children from traditionally constructed houses compared to more modern houses. Stunted children and underweight children were significantly more likely to have mild or moderate anaemia. During the transmission season, 13.7% of children had at least one episode of clinical malaria. There was no association between stunting and malaria incidence (odds ratio = 0.79, 95% CI: 0.60–1.05). Malaria was not associated with differences in weight or height gain. Conclusions Chronic malnutrition remains a problem in rural Gambia, particularly among the poor and Fula ethnic group, but it was not associated with an increased risk of malaria. Trial registration Trial registration: ISRCTN, ISRCTN01738840, registered: 27/08/2010 (Retrospectively registered).
EPrint Processing Status: Full text deposited in DRO